Empowering Economic Independence Of Ummah Based On The Sustainability Of Zakat - Syamsuri Syamsuri; Syamsuddin Arif; Luluk Wahyu Roficoh (AIBPM Publisher, 2019)
Zakat is one of the social financial instruments that has short-term goals to fulfill the main needs of mustahik, and long-term goals namely the economic independence of the ummah. Zakat institutions as public financial institutions managing community funds (zakat) has to be maintained efficiently and effectively to improve the communities welfare of zakat institutions. In this case, the quality of human resources (amil) is very influential in improving the management of zakat institutions. This study aims to explain the urgency of productive and professional zakat institutions and the ability to develop zakat’s management. This study used a qualitative method. Zakat’s management through zakat institutions in Indonesia contributes to national and global development significantly through empowerment programs that have been carried out and developed to achieve the sustainability of zakat